Pengaruh Imbangan Hijauan-Konsentrat dan Waktu Pemberian Ransum terhadap Produktivitas Kelinci Lokal Jantan - Qisthon, Arif (Politeknik Negeri Lampung., 2012)
This research was conducted to study the effect of ration with certain ratio of forage-concentrate and the time of feeding on productivity of male local rabbits. Eighteen rabbits were used in Completely Randomized Block Design with factorial pattern 3 x 2. The rabbits was devided in three groups based on its body weight. Body weight of the first group, the second group, and the third group respectively 1.085 -1.185 g, 1.200-1.365 g, and 1.380-1.530 g. There were two factors in this design. The first factor were ration with certain ratio of forage-concentrate (R). In that factor there was three treatmens, ration with ratio of forage-concentrate 60%:40 as the first treatment (R1), 50% :50% as the second treatment (R2), and 40%:60% as the third treatment (R3). The second factor was the time of feeding (W). There were two treatments in this factor, the time of feeding on day (at 06.00 am. up to 06.00 pm.) as the first treatment (W1) and on night (at 06.00 pm. up to 06.00 am.) as the second treatment (W2). The result indicated that there was no interaction (P>0.05) between ration with certain ratio of forage-concentrate and the time of feeding on feed consumption, average daily gain, and feed efficiency. The factor of ration with certain ratio of forage-concentrate affected (P<0.05) feed consumption, however didn?t affect (P>0.05) average daily gain and feed efficiency. Feed consumption of the rabbits that got treatment ration with ratio of forage-concentrate 40:60% (R3) was the lowest. The time of feeding didn?t affect (P>0.05) feed consumption, average daily gain, and feed efficiency. Keywords: Forage, concentrate, ration, rabbits